DESAIN SGRNA DAN PRODUKSI KOMPLEKS CAS9-RNP UNTUK EDIT GENOM BEBAS TRANSGENIK GEN EIF4E CAPSICUM ANNUUM L. - Josefanny
As of 2019, Indonesia experienced a decrease in the quantity of production of chili plants (Capsicum annuum L.) compared to 2018. This decrease was partly due to the high susceptibility of Capsicum annuum L. towards pathogens such as Potyvirus. eIF4E protein is known to aid Potyvirus replication in plant cells, hence the knockout of this gene is considered to increase the resistance of chili plants towards Potyvirus. Increasing plant resistance using transgene-free methods such as CRISPR-Cas9 could be one of the solutions as it does not require the insertion of foreign genes. CRISPR-Cas9 gene editing system is composed of a protein with an endonuclease catalytic domain and an incorporated sgRNA that determines specificity of the Ribonucleoprotein (RNP) complex. Due to those, this research was conducted with the aim to design the sgRNA, to determine the optimum IPTG concentration to produce Cas9 protein, and confirm the produced Cas9-RNP in vitro endonuclease activity. To target the eIF4E of the chili plant one sgRNA was designed that works towards the three bases upstream of the 196th nucleotide which is the Protospacer Adjacent Motif (PAM) sequence. This target is also located at the first exon without any potential off-target. Cas9 production itself could be done using BL21(DE3) E. coli as its chassis using plasmid 4xNLS-pMJ915v2-sfGFP deposited at Addgene (#88921). In this plasmid, Cas9 protein expression is regulated by a T7 promoter that is inducible by IPTG. In this research, the optimum concentration of IPTG to induce an expression of functional Cas9 at the cytoplasmic fraction was 500 ?M. The purification process showed that Cas9 protein was obtained up to the second fraction of elution (2 mL) using Ni-NTA purification column. Unfortunately, it was not possible to separate the Cas9 protein only by relying on the His-tag due to the presence of lots of untargeted proteins that could be seen after concentrating it through protein ultrafiltration. Based on Electrophoretic Mobility Shift Assay (EMSA) we observed that Cas9-RNP complexes were successfully formed. Both Cas9 proteins with or without Maltose Binding Protein (MBP) which was removed using TEV protease had similar in vitro endonuclease activity towards eIF4E. In future research, it is recommended to test the in vivo activity and optimize the purification process of Cas9 protein